Weighted Complex Network Analysis of the Different Patterns of Metro Traffic Flows on Weekday and Weekend - Jia Feng; Xiamiao Li; Baohua Mao; Qi Xu; Yun Bai (Discrete Dynamics in Nature and Society)
We present a multilayer model to characterize the weekday and weekend patterns in terms of the spatiotemporal flow size distributions in subway networks, based on trip data and operation timetables obtained from the Beijing Subway System. We also investigate the disparity of incoming and outgoing flows at a given station to describe the different spatial structure performance between transfer and nontransfer stations. In addition, we describe the essential interactions between PFN and TFN by defining an indicator, real load. By comparing with the two patterns on weekday and weekend, we found that the substantial trends have roughly the same form, with noticeable lower sizes of flows on weekend ascribed to the essential characteristics of travel demand.